2018
DOI: 10.1155/2018/6724818
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography versus Dye Angiography in Age-Related Macular Degeneration: Sensitivity and Specificity Analysis

Abstract: Introduction Optical coherence tomography angiography (OCTA) could be a valid tool to detect choroidal neovascularization (CNV) in neovascular age-related macular degeneration (nAMD), allowing the analysis of the type, the morphology, and the extension of CNV in most of the cases. Purpose To determine the sensitivity and specificity of OCTA in detecting CNV secondary to nAMD, compared to fluorescein angiography (FA) and indocyanine green angiography (ICGA). Methods Prospective observational study. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…It provides a volume imaging tool that allows further understanding of the normative human retinal vascular anatomy and physiology, displays pathological and disease progression, 1 and has a higher specificity and sensitivity in detecting some ocular vasculopathies. 2 , 3…”
Section: Introductionmentioning
confidence: 99%
“…It provides a volume imaging tool that allows further understanding of the normative human retinal vascular anatomy and physiology, displays pathological and disease progression, 1 and has a higher specificity and sensitivity in detecting some ocular vasculopathies. 2 , 3…”
Section: Introductionmentioning
confidence: 99%
“…Among 86 eyes, 46.4% (26/56) had well-circumscribed vessels while 53.6% (30/56) revealed poorly circumscribed vessels [11]. The study done by Nikolopoulou et al reported that OCTA had sensitivity of 88% and specificity of 90% [20]. Another study reported sensitivity and specificity of OCTA to be 89.2% and 93.3%, respectively [13].…”
Section: Discussionmentioning
confidence: 98%
“…Traditionally, the age of 40 years has been established as the age of onset of the classic ophthalmological alterations, although other pathologies such as macular alterations are more common beyond 50 years, so these changes in the choroid can be a predictive factor of future clinical alterations [ 7 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%